Óxidos cerâmicos a base de SrTiO3 e substituídos com Ferro/Prata – Caracterização Estrutural - AZEVEDO, Sérgio Alves de (2015)
Strontium titanate, SrTiO3 (ST) is a mixed oxide from the group of perovskites, has a cubic structure and a band gap of 3.2 eV. In this study systems SrTiO3(ST), SrTi0,90Fe0,10O3(STF), Sr0,90Ag0,10TiO3(SAT) and Sr0,95Ag0,05Ti0,90Fe0,10O3(SATF) were synthesized by the Pechini method in which the same, favor the production of nanostructured materials with a high stoichiometric accordingly. The precursors used were titanium isopropoxide, citric acid, strontium nitrate, ferric nitrate, silver nitrate and ethylene glycol. For the formation of the precursor powder, the resin is calcined at 300 °C for 1 hour with a ramp of 10 °C min-1. The precursor powder was characterized by TG/DTA. For the formation of calcined systems we used different temperatures of 400 °C / 500 °C/ 600 °C/ 700 °C/ 2h with a ramp of 10 °C min-1. The sample composition was calcined in ST 550 °C/ 2h to examine the formation of the phase. The samples were characterized by X-Ray Diffraction (XRD) spectroscopy, FTIR, UV-Vis spectroscopy, Raman spectroscopy and B.E.T. the sample STF showed a peak shift DTA higher intensity to lower temperature, resulting in a more rapid decomposition. The x-ray diffractograms show the formation of perovskite phase at low temperature of 600 °C with secondary phase SrCO3 and TiO2, the SAT and SATF samples occurred and formation of metal pranta as a secondary phase. Infrared spectra show that the material exhibits short-range organization and having SrCO3 as a secondary phase. Raman spectra show first order band which is characteristic of tetragonal structure ST. The samples are mesoporous, the substitution Ti / Fe and Sr / Ag promoted the reduction of the surface area of the samples. The addition of iron as a substituent ST caused a reduction of the optical band gap 3.21(2) to 2.31(2) in PBS and 2.16(1) composition in SATF composition. It can be concluded that the method is efficient in the synthesis of structural organization samples with short and long range, using calcination temperatures above 600 °C, and that the substitution by Ti/Fe promotes the reduction of the band gap and the surface area of the ST.